The situation of electronic Administration at the local level by the light of two reports. Particular attention to the case of Aragon - Magallón-Salegui, Jaime (Revista de Estudios de la Administración Local y Autonómica, 2024)
Objectives: There are various obligations to comply with in matters of electronic administration by public administrations, in accordance with Laws 39 and 40/2015, which included a decided commitment to the electronic processing of procedures. Objective whose achievement was postponed through successive vacatio legis until April 2, 2021, the date of entry into force of the regulatory development in this matter with Royal Decree 203/2021. Methodology: the study is based on academic literature, the European and national regulatory framework on this issue and several reports about the state of implementation with obligations regarding electronic administration, focusing on local administrations, particularly in Aragon. Results: There has been an improvement in the implementation of the various components of eGovernment by local administrations, a holistic concept that encompasses more than the mere incorporation of equipment, although there is still an uneven fulfilment of their obligations in this area. Conclusions: Given that the standard of compliance is the same for all administrations, it is necessary to strengthen collaboration with local administrations in order to reduce the existing gap.